ACSM'S Resources for the Exercise Physiologist : A Practical Guide for the Health Fitness Professional - Gordon, Benjamin Thomas; Chambliss, Heather; Durstine, J. Larry; Jett, David M.; Ross, Leanna M. (Wolters Kluwer, 2022)
"An essential preparation book for the ACSM Certified Exercise Physiologist examination, ACSM's Resources for the Exercise Physiologist, 3rd Edition, is an essential volume for certification candidates and practicing Exercise Physiologists looking to boost their exam confidence and achieve success in practice. This updated edition is fully aligned with the eleventh edition of ACSM's Guidelines for Exercise Testing and Prescription and reflects the most current standards and practices in exercise physiology. Published by the American College of Sports Medicine, this practical resource is organized around the scope of ACSM-EP practice domains. A clear introduction to understanding exercise, physical activity, and pre-exercise screening opens the book, followed by thorough coverage of assessment and programming for healthy populations, assessment and programming for special populations, counseling and behavioral strategies for encouraging exercises, and legal, management and professional issues relevant to practice.Updated content aligned with the 11th edition of ACSM's Guidelines for Exercise Testing and Prescription prepares students for exam success and equips prospective and practicing EPs with the foundation for confident, competent clinical practice.Chapter objectives keep students focused on essential information.How To boxes walk students step-by-step through commonly performed assessments.Exercise is Medicine boxes familiarize students with relevant research and highlight exercise's role in improving health.Case Studies provide essential practice applying knowledge to commonly encountered scenarios.Open-ended questions at the end of each chapter encourage critical thinking and test students' comprehension of chapter content.eBook available. Fast, smart, and convenient, today's eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more"--